h.hofstede (h.hofstede@hogeland.nl)

       
1. a. 2x2 - 48x + 60
2(x2 - 24x + 30)
2(x2 - 24x + 144 - 144 + 30)
2((x - 12)2 - 114)
2(x - 12)2 - 228
 
       
  b. x2 + 4x - 12
x2 + 4x + 4 - 4 - 12
(x + 2)2 - 16
 
       
  c. -5x2 - 20x - 10
-5(x2 + 4x + 2)
-5(x2 + 4x + 4 - 4 + 2)
-5((x + 2)2 - 2)
-5(x + 2)2 + 10
 
       
  d. 18 - x2 + 2x
-x
2 + 2x + 18
-(x2 - 2x - 18)
-(x2 - 2x + 1 - 1 - 18)
-((x - 1)2 - 19)
-(x- 1)2 + 19
 
       
2. a. 6x2 - 24x - 48 = 0
x2 - 4x - 8 = 0
x2 - 4x + 4 - 4 - 8 = 0
(x - 2)2 - 12 = 0
(x - 2)2  = 12
x - 2 = √12  ∨  x - 2 = -√12
x = 2 + √12  x = 2 - √12 
 
       
  b. x2 + 10x = 90
x2 + 10x - 90 = 0
x2 + 10x + 25 - 25 - 90 = 0
(x + 5)2 - 115 = 0
(x + 5)2 = 115
x + 5 = √115   ∨   x + 5 = -√115
x = -5 + √115   ∨   x = -5 - √115
 
       
  c. 2x2  + 10x + 6,5 = 0
2(x2 + 5x + 3,25) = 0
2(x2 + 5x + 6,25 - 6,25 + 3,25) = 0
2((x + 2,5)2 - 3) = 0
2(x + 2,5)2 - 6 = 0
2(x + 2,5)2 = 6
(x + 2,5)2  = 3
x + 2,5 = √3   ∨   x + 2,5 = -√3
x = -2,5 + √3  ∨   x = -2,5 - √3
 
       
3. ax2 + bx + c = 0
x2 + b/a x + c/a = 0

De helft van b/a is  b/2a  en het kwadraat daarvan is  b/4a :
x2 + b/a x  + b/4a  - b/4a  + c/a = 0
(x b/2a )2 - b/4a  + c/a  = 0
(x b/2a )2 = b/4a  - c/a
 
  √(4a2) = 2a of -2a  maar omdat er voor staat doet dat er niet toe en mogen we best gewoon 2a nemen.
 
       

h.hofstede (h.hofstede@hogeland.nl)